Development of an Electronic Brick Bonding Module Using the Autocad Program for Students - Mizian, Zuhdi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2023)
This research aims to develop an electronic AutoCAD learning module for drawing brick ties as an effort to increase the effectiveness of learning at Vocation High School 2 Merangin. The research method used is the Lee and Owens development model which consists of analysis, design, development, implementation and evaluation. The results of this research show that the AutoCAD learning module developed received a positive response from experts and students. This module is effective in improving students' understanding and skills in drawing brick ties using AutoCAD software. The novelty of this research lies in the development of interactive and interesting electronic modules to facilitate more effective and interesting learning. The implications of this research are increasing student motivation and interest in learning as well as increasing the quality of learning at Vocation High School 2 Merangin. Thus, the use of this AutoCAD learning module can make a positive contribution to improving the quality of education in the field of building engineering. The results of this research indicate that the development of an AutoCAD learning module can be an effective solution in overcoming challenges in learning technical drawing, especially in drawing brick ties. Therefore, it is hoped that the use of this module can be an innovative and efficient learning alternative in vocational high schools, as well as making a positive contribution in improving students' skills in technical drawing and their preparation for the world of work.